Comparison of three targeted approaches to screening for abdominal aortic aneurysm based on cardiovascular risk. Issue 9 (August 2016) - Jones, G.T.; Hill, B. G.; Curtis, N.; Kabir, T. D.; Wong, L. E.; Tilyard, M. W.; Williams, M. J. A.; van Rij, A. M.
Abstract: Background: Abdominal aortic aneurysm (AAA) continues to be a significant health burden yet few countries have implemented a comprehensive screening programme. Screening typically places emphasis on men aged over 65 years; however, there is concern that other at‐risk groups may be underidentified. The present study examined three potential screening strategies based on cardiovascular risk. Methods: The prevalence of AAA was determined by abdominal ultrasound imaging in over 50‐year‐olds of either sex undergoing coronary angiography, vascular laboratory assessment of peripheral arterial disease, or community‐based cardiovascular disease (CVD) event risk assessment. A fourth group, consisting of volunteers aged over 60 years who had no symptoms or signs of cardiovascular disease, was used as a comparator group. Results: A total AAA prevalence of 4·4 per cent was detected across all three strategies (137 of 3142 individuals), compared with 1·0 per cent in the CVD‐free group. Male sex, age and smoking were all associated with greater AAA prevalence. Although AAA prevalence was lowest using the community‐based strategy, those with an AAA detected were on average 7 years younger than those with AAAs detected with the other two strategies ( P  < 0·001). Conclusion: Different strategies, based on CVD risk, resulted in AAA prevalence rates that were significantly greater than that in CVD‐free individuals. This may provide opportunities for a targeted approach to community AAA screening in parts of the world where more sophisticated national screening programmes do not exist. Abstract : Supports a targeted approach